Temporal lobe evolution in Javanese Homo erectus and African Homo ergaster: Inferences from the cranial base. (30th November 2021) - Pearson, Alannah; Polly, P. David; Bruner, Emiliano
Abstract: Increased brain size is a characteristic of the Homo erectus hypodigm compared to early fossil hominins with changes in cerebral reorganization of evolutionary importance for the genus Homo . The close spatial proximity of the temporal lobes of the brain to the cranial base, specifically, the middle cranial fossa (MCF), provides inference of temporal lobe evolution. To date, differences in MCF proportions and relative scaling in the H. erectus hypodigm compared to extant Homo sapiens is unknown. A total sample (n = 51) of cranial Computed Tomography scans (CT) from extant H. sapiens and fossil specimens attributed to African Homo ergaster and Javanese H. erectus were generated into three-dimensional (3D) virtual models with three linear metrics digitally measured on the MCF and two metrics to approximate cranial size. Reduced Major Axis (RMA) log-log regressions and resampling with permutations determined if relative MCF scaling in the fossil sample was greater than observed among extant H. sapiens. An increase or decrease in MCF proportions in the fossil sample compared to extant H. sapiens was used to determine potential changes in temporal lobe size. There were no differences in the allometric trend of relative MCF scaling with no statistically significant differences suggesting that the fossil sample were beyond the range observed for extant H. sapiens, but the effects of the small fossil sample size could not be excluded. However, relative MCF proportions showed extant H. sapiens had a larger MCF to relative to cranial size, while specimens attributed to Javanese H. erectus which had a relatively longer and wider MCF compared to African H. ergaster . These findings indicate that despite sampling limitations, the fossil sample did not show differences in allometric scaling compared to extant H. sapiens, but these specimens attributed to Javanese H. erectus and African H. ergaster share the same total cranial size but had different MCF proportions relative to cranial size. The paleoneurological implications are that these specimens attributed to Javanese H. erectus had longer and wider temporal lobes relative to total brain size compared to African H. ergaster suggesting different patterns of cerebrocranial organization within the Homo erectus hypodigm.